Avaliação in vitro e ex vivo da atividade antimicrobiana da pasta de hidróxido de cálcio associada à curcuma longa sobre candida albicans e enterococcus faecalis - Moreno, Sandriane (2020)
Pulp and periradicular pathologies are caused by the presence and persistence of microorganisms in the root canal system. In this sense, a necropulpectomy can use to eradicate or lessen the microorganisms most prevalent in persistent lesions, such as Enterococcus faecalis and Candida albicans. With the increase in effects and antimicrobial resistance to drugs used in the use of natural products extracted from plants, it was an extremely explored alternative in several areas of health. Among these, Curcuma longa products stand out due to their antimicrobial action. In endodontics, alternatives are sought for irrigation solutions and intracanal medications. Given this context, the objective of the present study was to analyze, in vitro and ex vivo, an antimicrobial activity of C. longa and its associations against these microorganisms. After extracting the substances from the rhizomes, disk diffusion tests were performed on the agar and microdilution in the heat; thus determining the Minimum Inhibitory Concentration (MIC) of the ethanolic extract of C. longa (62 μg mL) for E. faecalis and C. albicans (32 μg/mL). From the CIM, the Fractional Inhibitory Concentration Index (FICI) of the combination of calcium hydroxide plus ethanolic extract was determined. As combinations that obtained synergism were (128 μg/mL + 32 μg/mL) and (96 μg/mL + 16 μg/mL) for E. faecalis and C. albicans respectively. To check the toxicity of some substances used in the ex vivo test, a hemolysis test was performed. The ethanolic extract showed less toxicity, with a hemolysis index of 28.18%, in relation to the other tested substances. To perform the ex vivo tests, 120 extracted teeth were used, which were processed by selection, preparation, contamination and application of intracanal medications. The specimens were randomly allocated to four groups: one for negative control and other treatment. Group I (negative control: propylene glycol), group II (calcium hydroxide (Ca(OH)2)), group III (chlorhexidine gel 2%) and group IV (Ca(OH)2 with ethanolic extract of C. longa). After the incubation period of the microorganisms, in each specimen, samples were collected at two levels of dentin depth and a count of colony-forming units (cfu/mL) for each group. The data were analyzed using the Kruskal-Wallis statistical test with a significance level set at 5% (P≤0.05). There was a statistically significant reduction in the cfu/mL count of C. albicans between the negative control group and the other groups at a more superficial depth: group II (P=0.02), group III (P=0.001) and group IV (P=0.02). Only group III showed a statistically significant reduction in relation to other groups (P=0.01). In the dentin portion evaluated more internally, there was a statistically significant difference for groups III and IV (P=0.01) when compared with the negative control group. The ethanolic extract has antifungal activity and when associated with Ca(OH)2 it was able to improve the action in the same way as the intracanal medication.